Nanostructured and Photochromic Material for Environmental Detection of Metal Ions - Raphael C. L. Machado (Molecules, 2019)
Compared to conventional spectroscopy or chromatography analysis, chemical sensing based on colorimetric changes offers an alternative to monitor potential metal hazards in aqueous environment through rapid and low-cost colorimetric changes which can be easily interpreted. In this work poly(ethylene glycol) (PEG 2000) was modified with a carboxylic acid spiropyran (SPCOOH) derivate by Steglich esterification (PEGSP2). PEGSP2 was incorporated into a poly(-caprolactone) (PCL) polymer matrix by electrospinning technique to produce nanofibers with photochromic properties. Spectroscopic analysis, thermal gravimetric analysis (TGA), and differential scanning calorimetry (DSC) were used to characterize PEGSP2. Drop shape analysis (DSA) and scanning electronic microscopy (SEM) were used to characterize the electrospun (ES) nanofibers morphology. Several metal ions solutions relevant to environmental hazards were prepared to be spotted on the surface of ES nanofibers for photochromatic sensing. Among them, Mg2+, Ca2+, Zn2+, Cd2+, La3+, and Er3+ demonstrated orange fluorescence when exposed to UV light. ES nanofibers also presented higher wettability when compared to a pure PCL polymer matrix, which is critical for sensitivity. Eighteen metals ions could be detected on the electrospun material. Additionally, among all metal ions Fe3+ was the most sensitive one in solution, in a µmol L1 range.